Thelephora sikkimensis sp. nov. (Thelephoraceae) from the Eastern Himalayas (India) - Das, Kanad (2018)
Thelephoroid fungi are abundant ectotrophic symbionts in temperate forests worldwide.The state of Sikkim, in India, constitutes a hot spot of fungal diversity due to the occurrence ofmany ectomycorrhizal tree species. Collections of a stipitate thelephoroid species were found underCastanopsis hystrix in the district South of this state. Molecular and morphological analyses supportthe placement of these collections as a monophyletic unit that is proposed here as Thelephorasikkimensis sp. nov. This species is characterized by its pileate-stipitate basidiomes; zonate-hairypileus surface, papillate-odontoid hymenophore and large basidia [35?65 (infrequently up to 125)× 7-9 μm]. Morphological details of this new species are presented along with its phylogeneticaffinities estimated on nrITS-based analyses.